2021
DOI: 10.1038/s41598-021-89210-7
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury induces neuronal cell death by inducing TNF-α expression through the ASK1/p38 signaling pathway in microglia

Abstract: We recently found that tumor necrosis factor-α (TNF-α) may be involved in neuronal cell death induced by methylmercury in the mouse brain. Here, we examined the cells involved in the induction of TNF-α expression by methylmercury in the mouse brain by in situ hybridization. TNF-α-expressing cells were found throughout the brain and were identified as microglia by immunostaining for ionized calcium binding adaptor molecule 1 (Iba1). Methylmercury induced TNF-α expression in mouse primary microglia and mouse mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…BV-2 microglial cells were exposed to MeHg followed, or not, by stimulation with LPS, for 6 h. In the absence of LPS, microglial cells did not exhibit changes in the production and secretion of both pro-inflammatory cytokines when exposed to different MeHg concentrations. However, upon LPS stimulation, we observed a significant increase in IL-6 and TNF-α content, according to the previously observed in several studies ( Pinheiro et al, 2007 ; Toyama et al, 2021 ; Yuan et al, 2021 ). Moreover, treatment with 10 µM-MeHg significantly decreased the LPS-stimulated cytokines production and release.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…BV-2 microglial cells were exposed to MeHg followed, or not, by stimulation with LPS, for 6 h. In the absence of LPS, microglial cells did not exhibit changes in the production and secretion of both pro-inflammatory cytokines when exposed to different MeHg concentrations. However, upon LPS stimulation, we observed a significant increase in IL-6 and TNF-α content, according to the previously observed in several studies ( Pinheiro et al, 2007 ; Toyama et al, 2021 ; Yuan et al, 2021 ). Moreover, treatment with 10 µM-MeHg significantly decreased the LPS-stimulated cytokines production and release.…”
Section: Discussionsupporting
confidence: 91%
“…Several reports have highlighted discrepancies concerning IL-6 and TNF-α production and secretion during MeHg exposure in animal studies ( Toyama et al, 2021 ) and microglial cell lines ( Sass et al, 2001 ; Thameem Dheen et al, 2007 ; Ge et al, 2019 ). Indeed, in N9 microglial cells treated with several concentrations of MeHg for 8h, the results showed that 10 µM-MeHg induces a significant increase in IL-6 production ( Garg and Chang, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Human Protein Atlas database indicates that USP54 is highly expressed in oligodendrocytes and microglia, glial cells of the central nervous system, and is mainly distributed in mitochondria. We have recently found that excessive activation of microglia, immune cells in the brain, is involved in methylmercury-induced central nervous system damage (Hoshi et al, 2019;Toyama et al, 2021a). Because mitochondria are a main target organelle of methylmercury (Lee et al, 2016;Mori et al, 2011;Sato et al, 2020), USP54 might attenuate its toxicity by suppressing the inflammatory response in the brain induced by methylmercury through an unknown function in mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…The differences between these results may arise from differences in experimental conditions; however, the details are unknown. Other cytokines, such as TNF-α 52,54,66,69) and IL-1β, 52,66) are also increased following MeHg exposure, as revealed by mRNA and protein assays. However, reduced expression of TNF-α mRNA following low-dose MeHg exposure 52) and no change of TNF-α following MeHg exposure 53) have also been reported.…”
Section: Methylmercury-induced Release Of Proinflammatory Cytokines F...mentioning
confidence: 94%